Navigating Your Acute Heart Failure Patient in Emergency and Pre-Discharge Phase - Budi Yuli Setianto (ACI (Acta Cardiologia Indonesiana), 2019)
Heart failure (HF) leads to frequent hospitalizations. The presence of re-hospitalization risk among patientshospitalized for heart failure is important, especially hemodynamic instability and neurohormonal over activation. ARNI is needed to restore the balance of neurohormonal system in HF. PARADIGM-HF study provide insight on long term benefit of ARNI (i.e. sacubitril/valsartan) in ambulatory setting. How is the evidence of ARNI use for in hospitalization phase of HF? PIONEER and TRANSITION showed that initiation of sacubitril/valsartan shortly after an ADHF event is feasible and well tolerated. In-hospital initiation of sacubitril/valsartan is associated with early and sustained improvements in biomarkers of cardiac wall stress and myocardial injury, indicating pathophysiological benefits in a wide range of HFrEF patients.